Prototype of CO, CO2 , UV Light, Temperature and Humidity Detection Device Based on IoT and Solar Cells - Tejaleksono, Gunawan; Notosudjono, Didik; Machdi, Agustini Rodiah; Adzikri, Fikri; Rahayu, Andri Ulus (Teknik Elektro Universitas Siliwangi, 2024)
Exposure to air pollution, excessive ultraviolet (UV) light, and changes in environmental temperature and humidity can have serious impacts on human health. Therefore, a tool design was created that combines Solar Cell-based technology and the Internet of Things (IoT) to detect potential dangers from air pollution, exposure to UV rays, and changes in environmental temperature and humidity. This tool uses an ESP32 microcontroller as its brain, which allows data to be collected from the sensors used. The sensors used include the MQ2 Sensor for toxic gas detection, the MQ135 Sensor for CO2 pollutant gas detection, the UV Sensor for monitoring harmful UV radiation, and the DHT11 Sensor for measuring environmental temperature and humidity. The information collected by these sensors is displayed in real-time via an OLED display, giving users an instant understanding of the level of danger that may exist in their surroundings. Apart from that, this tool uses Solar Cells as a power source, so it can operate independently and is environmentally friendly. This tool has great potential for use in a variety of environments, including residential areas, work spaces and open areas. It helps society as a whole to maintain their health and safety by providing accurate and real-time information about the dangers that may be around them. KEYWORDS: DHT-11, ESP-32, GUVA S12SD, Internet of Things (IoT), MQ-2, MQ-135 Solar Cell.